DETERMINATION OF SOME ESSENTIAL AMINO ACIDS IN SEVERAL UNCOOKED AND COOKED MEXICAN FOODSTUFFS - TORRE CALVO, JOSE DE LA; MASSIEU H , GUILLERMO; GUZMAN, G JESUS; CRAVIOTO, RENE O (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1977)
A new locality, near Mexico City, is reported where P mexicanum can be found in Sceloporus ferrariperezi and S m microlepidotus, the latter being a new natural host The parasitic forms in the circulating blood of both hosts are descr and the evolutio
J NUTR
Keywords: DETERMINATION, AMINO, ACIDS, UNCOOKED, COOKED, MEXICAN, FOODSTUFFS; CIENCIAS MEDICAS; CIENCIAS DE LA NUTRICION; DIGESTION